Bacteriocin activity of Lactobacillus brevis and Lactobacillus paracasei ssp. paracasei. Issue 9 (31st July 2019) - Iseppi, Ramona; Messi, Patrizia; Camellini, Stefania; Sabia, Carla
Abstract : Methodology . Biochemical and molecular methods were used to identify 100 lactobacilli isolated from rectal swabs. Among these, L. paracasei ssp. paracasei LP5 and L. brevis LP9 showed significant antibacterial activity against S. agalactiae and L. monocytogenes . Accordingly, characterization of their bacteriocins, BacLP5 and BacLP9, was conducted to obtain information on their kinetic production, sensitivity to chemico-physical parameters and molecular weight. To investigate the possible use of the two Lactobacillus strains as probiotics, their gastrointestinal resistance, cellular adhesiveness and sensitivity to antibiotics were also studied. Results . The obtained data show that BacLP5 and BacLP9 most likely belong to class II bacteriocins and both have a molecular weight of approximately 3 kDa. The production of BacLP5 and BacLP9 started after 4 h (40 and 80 AU ml −1 ), respectively. Both of the Lactobacillus strains survived gastric and intestinal juices well and showed adhesive capability on HEp-2 cells. Conclusion . Due to their peculiar antimicrobial characteristics, L. paracasei ssp. paracasei LP5 and L. brevis LP9 are suitable for use in the treatment of vaginal disorders, through both oral and transvaginal administration.